2020
DOI: 10.17358/ijbe.6.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Do Website Quality, Fashion Consciousness, and Sales Promotion Increase Impulse Buying Behavior of E-Commerce Buyers?

Abstract: The prevalence of online shopping also gave rise to irrational shopping behavior like impulse buying, which makes up a large share of e-retailer revenue. This study's objective was to analyze the factors that affect impulse buying (i.e., website quality, sales promotion, and fashion consciousness) within the context of apparel/fashion product purchase. Besides, this study also sought to examine the role of sales promotion in moderating the relationship between website quality and impulse buying. An online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 33 publications
(71 reference statements)
0
35
0
19
Order By: Relevance
“…Both the investigated psychological and marketing variables have demonstrated a direct significant influence towards the clothing interest among Generation Y consumers. The findings hereby offered reinforced support on earlier literature which investigate the Notes: FI = Fashion innovativeness; SC = Self-concept; FC = Fashion consciousness; NFU = Need for uniqueness; SMM = Social media marketing; Fads = Fashion advertisement; Cint = Clothing interest; PI = Purchase intention; Att = Product attitude; Conf = Self-confidence, ns = not significant; **and *denote significant at 99% and 95% confidence level, respectively dimensions of fashion innovativeness (Park et al, 2007;Rahman et al, 2014), self-concept (Bahri-Ammari et al, 2020;Nyadzayo et al, 2020), fashion consciousness (Khan et al, 2019;Wiranata and Hananto, 2020), NFU (Latter et al, 2010;Workman and Caldwell, 2007), SMM (Scuotto et al, 2017) and fashion advertisement (Chu et al, 2019) in affecting market consumption. However, researchers including Park and Noh (2011) have suggested a contradicted view following the absent of direct causation between fashion innovativeness and creativity of advertised message on consumption intention.…”
Section: Psychological and Marketing Factorsmentioning
confidence: 99%
“…Both the investigated psychological and marketing variables have demonstrated a direct significant influence towards the clothing interest among Generation Y consumers. The findings hereby offered reinforced support on earlier literature which investigate the Notes: FI = Fashion innovativeness; SC = Self-concept; FC = Fashion consciousness; NFU = Need for uniqueness; SMM = Social media marketing; Fads = Fashion advertisement; Cint = Clothing interest; PI = Purchase intention; Att = Product attitude; Conf = Self-confidence, ns = not significant; **and *denote significant at 99% and 95% confidence level, respectively dimensions of fashion innovativeness (Park et al, 2007;Rahman et al, 2014), self-concept (Bahri-Ammari et al, 2020;Nyadzayo et al, 2020), fashion consciousness (Khan et al, 2019;Wiranata and Hananto, 2020), NFU (Latter et al, 2010;Workman and Caldwell, 2007), SMM (Scuotto et al, 2017) and fashion advertisement (Chu et al, 2019) in affecting market consumption. However, researchers including Park and Noh (2011) have suggested a contradicted view following the absent of direct causation between fashion innovativeness and creativity of advertised message on consumption intention.…”
Section: Psychological and Marketing Factorsmentioning
confidence: 99%
“…The results of the study are also similar to the inferences made by Loxton et al (2020) whereby, it was concluded that consumer behaviour during the COVID-19 crisis tends to be consistent with the actions seen during historical shock events. Addo et al (2020), Kim (2020) and Wiranata and Hananto (2020) found similar consumer behaviour patterns during COVID-19 in case of United States. Garrett (2020) also discovered that COVID-19 had a significant impact on individuals, and that customers in the United States resorted to impulse purchases during the crisis.…”
Section: Stocking and Impulse Buying Behaviourmentioning
confidence: 57%
“…In moments of uncertainty, customer behaviour theories show how people try to achieve a sense of control by acquiring products and by indulging in panic buying (Yuen et al, 2020). Impulse purchasing behaviour has increased significantly in the United States and other parts of the world as a result of COVID-19 pandemic (Kim, 2020;Wiranata and Hananto, 2020;Addo, 2020). Garrett (2020) also found that COVID-19 has had a huge effect on individuals, and that consumers in the United States engaged in impulse buying during this crisis situation.…”
Section: Impulse Buying Behaviourmentioning
confidence: 99%
“…Several studies have been carried out regarding the use of websites as promotional media, including research focused on evaluating the quality of websites created and used as promotional media (Aydin and Kahraman, 2012). The same thing is stated: website media is very effective for promoting and marketing the evaluation of products being sold (Wiranata and Hananto, 2020). Other researchers stated that the website is a means to optimize promotion in small businesses (Simmons et al, 2011).…”
Section: Introductionmentioning
confidence: 91%